Light absorber, preparation method and application thereof

CN122945189APending Publication Date: 2026-10-20TIANFU JIANGXI LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611347262.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]为了解决现有光吸收体难以兼顾吸收效果、机械稳定性和大批量生产的技术问题,本发明提供一种光吸收体及制备方法、应用

Benefits of technology

1.本发明实施例提供的一种光吸收体,包括吸收层以及设置于吸收层表面的减反层;所述吸收层由聚合物基体和纳米吸光单元复合组成,以聚合物基体为连续相、引入高消光系数的纳米吸光单元形成复合体系,负责入射光能量的体相耗散。所述减反层包括依次层叠的多个不同折射率的子层,负责消除空气与吸收层界面间因折射率突变引起的菲涅尔反射。区别于现有技术,本发明将吸收和减反这两个功能解耦至独立物理层,吸收层的消光系数不受减反层材料的约束,减反层的减反带宽不受吸收层材料体系选择的限制,从而在更宽的光波段范围内实现稳定的光吸收性能。并且,本发明实施例提供的光吸收体,表面为连续致密薄膜结构,没有自由支撑或半自由支撑的微纳结构,机械稳定性高,不易因环境影响而损失性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to a light absorber, its preparation method, and its applications. The light absorber comprises an absorption layer and an antireflection layer; the absorption layer is composed of a polymer matrix and nano-absorbing units; the antireflection layer comprises multiple sub-layers stacked sequentially, each sub-layer being composed of a polymer matrix and oxide particles. By adjusting the type and / or mass fraction of the oxide particles, each sub-layer has a different refractive index, exhibiting a gradient change along the stacking direction. The preparation employs a wet process. First, nano-absorbing units are mixed with the polymer matrix, coated, and cured to form the absorption layer. Then, the target refractive index and target thickness of each sub-layer are obtained using TMM and a global optimization algorithm. Based on this, multiple sub-layer coating solutions are prepared and coated and cured layer by layer to construct the antireflection layer. This light absorber can achieve an average reflectance of less than 1% in the visible light band, and the all-wet process supports low-temperature film deposition under normal pressure and large-area continuous production, making it applicable to photoelectric detection, imaging displays, semiconductor devices, and precision optical systems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of light absorber technology, and particularly to a light absorber, its preparation method, and its application. Background Technology

[0002] With the rapid development of photoelectric detection, imaging display, semiconductor devices, and precision optical systems, the demand for materials that achieve efficient absorption, suppress interface reflection, and reduce stray light interference over a wide wavelength range is becoming increasingly urgent. Light absorbers, due to their ability to achieve extremely low or even near-zero reflection over a wide wavelength range and under multiple incident conditions, are considered one of the important functional materials for improving the signal-to-noise ratio and device performance of optical systems. Current research on light absorbers mainly focuses on enhancing the multiple scattering and localization of light within the material by constructing surface micron or nanoscale structural units, such as high aspect ratio arrays, porous structures, or periodic / quasi-periodic micro / nano structures, thereby improving the overall light absorption efficiency.

[0003] However, the aforementioned technical approaches typically rely on freely supported or semi-freely supported micro / nano structures to achieve light capture, which significantly limits their structural stability and engineering applicability. On the one hand, these micro / nano structures are finely sized and loosely arranged, making them prone to deformation, collapse, or structural degradation under external impact, thermal cycling, or environmental changes. On the other hand, their fabrication processes often involve complex procedures such as high-temperature treatment, vacuum deposition, plasma etching, or pre-template replication, requiring high equipment conditions and process compatibility, making direct integration with existing semiconductor manufacturing processes such as thin-film deposition, photolithography, and packaging difficult. Furthermore, due to the limited interfacial bonding between the structure and the substrate, these light absorbers are prone to insufficient adhesion and poor performance consistency in large-area fabrication and device-level applications, hindering their engineering and large-scale application.

[0004] Specifically, existing representative technologies mainly rely on mesoscale array structures (such as high aspect ratio carbon nanotube arrays, cylindrical or conical discrete geometric units) to achieve light capture. These schemes achieve both impedance matching and multiple scattering absorption within the same structure using a single geometric parameter (such as structural volume fraction, array period, or height). However, their drawback is that impedance matching performance and scattering absorption capability are coupled to the same geometric parameter, making independent optimization difficult. Furthermore, the fabrication of these structures relies on vacuum dry processes such as magnetron sputtering, thermal evaporation, and electron beam evaporation, or patterning processes such as photolithography and plasma etching. These methods involve high equipment investment, narrow process windows, and lack engineering feasibility under ambient pressure and low-temperature fabrication conditions. In addition, existing dry multilayer deposition light-absorbing thin film schemes typically use a single-layer, single-refractive-index structure for the antireflection layer, lacking gradient profile optimization and limiting broadband antireflection capabilities, corresponding to a reflectivity of approximately 2%–3%. Meanwhile, transmissive antireflective film systems have small extinction coefficients and poor light energy absorption capabilities in each layer, failing to achieve perfect absorption. Therefore, how to achieve near-zero reflection and efficient light absorption in the target wavelength band (visible light band) using a continuous dense thin film structure under normal pressure and low temperature conditions, while ensuring mechanical stability and process compatibility for large-area fabrication, is a technical problem that urgently needs to be solved. Summary of the Invention

[0005] To address the technical challenges of existing light absorbers in simultaneously achieving high absorption efficiency, mechanical stability, and mass production, this invention provides a light absorber, its preparation method, and its applications. Without relying on free-supporting micro / nano structures or complex high-temperature or vacuum processes, it effectively suppresses interfacial reflection and improves light absorption efficiency, meeting the application requirements for large-area fabrication and integration with mainstream manufacturing processes.

[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a light absorber, comprising an absorption layer and an antireflection layer disposed on the surface of the absorption layer; the absorption layer is composed of a polymer matrix and nano-absorbing units; the refractive index of the absorption layer is 1.48-1.55; the antireflection layer comprises a plurality of sublayers stacked sequentially; the sublayers are composed of a polymer matrix and oxide particles, and by designing different types and / or mass fractions of oxide particles, each sublayer has a different refractive index, and the refractive index of each sublayer varies in a gradient along the stacking direction; the refractive index of each sublayer is 1.20-1.91.

[0007] Preferably, the light absorber further includes an outer layer; the outer layer is disposed on the side of the antireflection layer opposite to the absorption layer; the outer layer is a MgF2 thin film.

[0008] Preferably, the light absorber comprises an absorption layer, a first sublayer, a second sublayer, and an outer layer stacked sequentially; the absorption layer is a composite film incorporating carbon black nanoparticles, with a thickness of 300nm-800nm, and an equivalent complex refractive index of 1.48-1.55 real part and 0.002-0.01 imaginary part in the 380nm-780nm optical wavelength range; the first sublayer is a composite film incorporating titanium dioxide, wherein the titanium dioxide has an average particle size of 10nm-20nm and a mass fraction of 30wt%-40wt%; the thickness of the first sublayer is 70nm-80nm. Within the optical wavelength range of 380nm-780nm, the refractive index is 1.60-1.64; the second sublayer is a composite thin film incorporating titanium dioxide, wherein the average particle size of the titanium dioxide is 10nm-20nm and the mass fraction is 68wt%-78wt%; the thickness of the second sublayer is 125nm-145nm, and the refractive index is 1.89-1.91 within the optical wavelength range of 380nm-780nm; the outer layer is a MgF2 thin film, the thickness of which is 80nm-110nm, and the refractive index is 1.38 within the optical wavelength range of 380nm-780nm. All refractive indices refer to the refractive index at λ=550 nm.

[0009] To solve the above-mentioned technical problems, the present invention provides another technical solution as follows: a method for preparing a light absorber, comprising the following steps: preparing an absorption layer using a wet method: preparing an absorption layer coating liquid by combining nano-absorbing units with a polymer matrix; coating the absorption layer coating liquid onto the surface of a substrate and curing it to form an absorption layer; preparing an antireflection layer using a wet method: obtaining the target refractive index and target thickness of each sublayer in the antireflection layer through TMM and a global optimization algorithm; mixing oxide particles with the polymer matrix according to the target refractive index, and obtaining multiple sublayer coating liquids by adjusting the type and / or mass fraction of the oxide particles; and coating and curing multiple sublayer coating liquids on the side of the absorption layer opposite to the substrate according to the target thickness, constructing multiple sublayers with different refractive indices, and an antireflection layer composed of multiple sublayers.

[0010] Preferably, the absorption layer is prepared by a wet process, specifically including the following steps: mixing nano-absorbing units with a polymer matrix to obtain an absorption layer mixture; the nano-absorbing units account for 0.5 wt%-10 wt% of the total mass of the absorption layer mixture; adding a curing agent to the absorption layer mixture and mixing it evenly to obtain an absorption layer coating liquid with a dynamic viscosity of 50 mPa·s-500 mPa·s; and coating the absorption layer coating liquid onto the surface of the substrate and curing it to form the absorption layer.

[0011] Preferably, the nano-absorbing unit is mixed with a polymer matrix to obtain an absorption layer mixture, specifically including the following steps: dissolving the polymer matrix in a mixed solvent to prepare a polymer matrix solution, wherein the solid content of the polymer matrix is ​​15wt%-30wt%; performing surface functionalization treatment on the nano-absorbing unit to form an organic modification layer containing reactive functional groups on the surface of the nano-absorbing unit, wherein the reactive functional groups are selected from at least one of carbon-carbon double bonds, carboxyl groups, hydroxyl groups, and silanol groups; adding the surface-functionalized nano-absorbing unit to the mixed solvent, and centrifuging to obtain a nano-absorbing unit premix; placing the premix in an ultrasonic cell disruptor to break up the nano-absorbing unit aggregates through jet flow to achieve a primary particle dispersion state, thereby obtaining a nano-absorbing unit dispersion, wherein the polydispersity index of the primary particle dispersion state is not higher than 0.15; and adding the nano-absorbing unit dispersion to the polymer matrix solution and mixing to obtain the absorption layer mixture.

[0012] Preferably, the target refractive index and target thickness of each sublayer in the antireflection layer are obtained through TMM and a global optimization algorithm, specifically including the following steps: establishing a candidate set based on parameter combinations of fabricable refractive index and thickness of each sublayer; calculating the complex refractive index of the absorption layer based on the MG model and the volume fraction of nano-absorbing units in the absorption layer, and using the complex refractive index of the absorption layer as the terminal admittance; constructing an objective function with the refractive index and thickness of each sublayer as design variables, with the goal of obtaining the minimum average reflectance of the wavelength band where the light to be absorbed is located as the optimization direction; calculating the spectral reflectance of the parameter combinations in the candidate set using TMM, and integrating to obtain the average reflectance, which is used as the fitness in the global optimization algorithm; using the global optimization algorithm to find the parameter combination that minimizes the reflection loss of the light to be absorbed; and obtaining the target refractive index and target thickness of each sublayer after screening based on process feasibility.

[0013] Preferably, based on the target refractive index, oxide particles are mixed with a polymer matrix, and multiple sublayer coating solutions are obtained by adjusting the type and / or mass fraction of the oxide particles. Specifically, this includes the following steps: dissolving the polymer matrix in a mixed solvent to prepare a polymer matrix solution; surface-modifying the oxide particles; adding the surface-modified oxide particles to the mixed solvent, dispersing and mixing them to obtain an oxide particle dispersion; and weighing the oxide particle dispersion according to the target refractive index, and mixing the oxide particle dispersion with the polymer matrix to prepare multiple sublayer coating solutions capable of constructing sublayers with different refractive indices.

[0014] Preferably, the surface modification of the oxide particles specifically includes: modifying the surface of the oxide particles with a silane coupling agent and a phosphate dispersant; causing the silanol groups in the silane coupling agent to undergo a condensation reaction with the hydroxyl groups on the surface of the oxide particles to form covalent bonds; and causing the phosphate groups in the phosphate dispersant to form coordination bonds with the surface of the oxide particles.

[0015] To solve the above-mentioned technical problems, the present invention provides another technical solution as follows: the application of a light absorber in photoelectric detection, imaging display, semiconductor devices and precision optical systems.

[0016] Compared with the prior art, the light absorber, preparation method, and application provided by the present invention have the following beneficial effects: 1. An embodiment of the present invention provides a light absorber, comprising an absorption layer and an antireflection layer disposed on the surface of the absorption layer; the absorption layer is composed of a polymer matrix and nano-absorbing units, with the polymer matrix as the continuous phase and the nano-absorbing units with high extinction coefficients forming a composite system responsible for the bulk dissipation of incident light energy. The antireflection layer comprises multiple sublayers with different refractive indices stacked sequentially, responsible for eliminating Fresnel reflection caused by abrupt changes in refractive index at the interface between air and the absorption layer. Unlike existing technologies, the present invention decouples the absorption and antireflection functions to independent physical layers. The extinction coefficient of the absorption layer is not constrained by the antireflection layer material, and the antireflection bandwidth of the antireflection layer is not limited by the choice of the absorption layer material system, thereby achieving stable light absorption performance over a wider optical wavelength range. Furthermore, the light absorber provided in this embodiment has a continuous dense thin film structure on its surface, without freely supported or semi-freely supported micro / nano structures, exhibiting high mechanical stability and being less prone to performance loss due to environmental influences.

[0017] 2. The light absorber provided in this embodiment of the invention further includes an outer layer disposed on the side of the antireflection layer away from the absorption layer, wherein the outer layer is a MgF2 thin film. The refractive index of the MgF2 thin film is as low as 1.38, which is close to the refractive index of air (1.0). Disposing of the MgF2 thin film on the side of the antireflection layer away from the absorption layer can significantly reduce Fresnel reflection at the air-to-water interface. Compared with the prior art using a nanoporous structure as the outermost low-refractive-index layer, the dense MgF2 thin film has no pore defects, and exhibits superior mechanical strength, abrasion resistance, and anti-fouling ability, thus avoiding the collapse and performance loss of the porous structure in the prior art during use.

[0018] 3. The light absorber provided in this embodiment of the invention uses carbon black nanoparticles as light-absorbing units in the absorption layer. The real part of the equivalent complex refractive index is 1.48-1.55, and the imaginary part is 0.002-0.01. The real part of 1.48-1.55 provides a boundary refractive index that matches the antireflection layer, while the imaginary part of 0.002-0.01 provides a moderate light dissipation capability without causing excessive absorption that would cause the real part of the refractive index to deviate from the design value. Titanium dioxide is introduced as a refractive index adjusting component in both the first sublayer (refractive index 1.60-1.64, thickness 70nm-80nm) and the second sublayer (refractive index 1.89-1.91, thickness 125nm-145nm). Two target refractive indices are achieved by controlling the mass fraction of titanium dioxide (30wt%-40wt% and 68wt%-78wt%). The equivalent refractive index distribution corresponding to this stacking sequence is: air (1.00) → MgF2 outer layer (1.38) → second sublayer (1.89-1.91) → first sublayer (1.60-1.64) → absorption layer (1.48-1.55). This non-monotonic refractive index gradient, through the constructive / destructive interference effects between sublayer interfaces, achieves a better antireflection bandwidth and a lower minimum reflectance in the target wavelength band than monotonic stacking. An average reflectance of 0.43% is achieved in the 380nm-780nm visible light band, and due to the continuous and dense thin film structure of the surface, it exhibits high mechanical stability.

[0019] 4. An embodiment of the present invention provides a method for preparing a light absorber, comprising a wet method for preparing an absorption layer: preparing an absorption layer coating liquid by combining nano-absorbing units with a polymer matrix; coating the absorption layer coating liquid onto the substrate surface and curing it to form an absorption layer; and a wet method for preparing an antireflection layer: obtaining the target refractive index and target thickness of each sublayer in the antireflection layer through TMM and a global optimization algorithm; mixing oxide particles with the polymer matrix according to the target refractive index, and obtaining multiple sublayer coating liquids by adjusting the type and / or mass fraction of the oxide particles; and coating and curing multiple sublayer coating liquids on the side of the absorption layer opposite to the substrate according to the target thickness, constructing multiple sublayers with different refractive indices, and forming an antireflection layer composed of multiple sublayers. Unlike the PVD / CVD vacuum deposition (dry method) process commonly used in the prior art, the absorption layer and antireflection layer of the present invention can both be achieved by wet processes such as spin coating, blade coating, slot coating, or spray coating. In this embodiment of the invention, the film formation of each layer is completed under normal pressure and low temperature conditions, and supports continuous production. The equipment investment and operating energy consumption are low, which is conducive to large-scale manufacturing and cost control. Furthermore, the refractive index of each sublayer can be precisely controlled by adjusting the type and mass fraction of oxide particles. Compared with traditional dry deposition preparation, there is no need to change the deposition source or adjust the vacuum process parameters, making the process more flexible and the preparation more repeatable.

[0020] 5. An embodiment of the present invention provides a method for preparing a light absorber, wherein nano-absorbing units are mixed with a polymer matrix to obtain an absorption layer mixture; the nano-absorbing units account for 0.5wt%-10wt% of the total mass of the absorption layer mixture; within this range, the nano-absorbing units can provide sufficient extinction coefficient to achieve light energy dissipation, without causing particle agglomeration and increased film roughness due to excessive solid content. In this embodiment, a curing agent is added to the absorption layer mixture and mixed uniformly to obtain an absorption layer coating liquid with a dynamic viscosity of 50 mPa·s-500 mPa·s, which ensures the leveling and thickness uniformity of the wet film on the substrate surface. The absorption layer coating liquid is coated onto the substrate surface and cured; the reactive functional groups in the polymer matrix undergo a cross-linking reaction with the curing agent to form a dense cross-linked network. Therefore, the absorption layer obtained by this preparation method has excellent toughness and adhesion.

[0021] 6. The present invention provides a method for preparing a light absorber, which achieves uniform dispersion of nano-light-absorbing units at the primary particle level through surface functionalization treatment and multi-stage dispersion process. Due to their large specific surface area and high surface energy, nano-light-absorbing units are prone to secondary aggregation in polymer matrices driven by van der Waals forces. This invention first performs surface functionalization treatment on the nano-light-absorbing units, introducing an organic modification layer containing at least one reactive functional group (carbon-carbon double bond, carboxyl group, hydroxyl group, and silanol group) on the surface of the nano-light-absorbing units to reduce the surface energy of the nano-light-absorbing units and enhance their interfacial compatibility with the polymer matrix. Subsequently, a combination of centrifugal mixing and ultrasonic jet disruption is used to achieve macroscopic dispersion of the nano-light-absorbing units and initial breakup of the aggregates through high shear force. An ultrasonic cell disruptor further breaks up the nano-light-absorbing unit aggregates using microjets generated by acoustic cavitation effect, achieving a primary particle dispersion state, thereby resulting in a uniform size distribution of the nano-light-absorbing units.

[0022] 7. The present invention provides a method for fabricating a light absorber, which obtains the target refractive index and target thickness of each sublayer in the antireflection layer through TMM and global optimization algorithms. The present invention first establishes a candidate set based on the parameter combinations of the fabricable refractive index and thickness of each sublayer, limiting the search space to a range achievable in the process, thus avoiding unattainable refractive index or thickness values. Based on the MG model and the volume fraction of the nano-absorbing units in the absorption layer, the present invention calculates the complex refractive index of the absorption layer. The MG model fully incorporates the impedance characteristics and light absorption capacity of the absorption layer into the design, making the final measured reflectance closer to the design value. The present invention optimizes by achieving the minimum average reflectance in the wavelength band of the light to be absorbed. The optimization target is not an extremely low reflectance at a single wavelength, but rather the minimum average reflectance across the entire target wavelength band (e.g., 380nm–780nm), avoiding the common single-wavelength optimization trap (where a very deep contrast valley appears only at the design wavelength, and the reflectance at the edge wavelengths rises rapidly), thereby achieving wide-band antireflection. This invention utilizes TMM (Transient Motion Model) to calculate spectral reflectance for parameter combinations in a candidate set, and integrates to obtain the average reflectance, which serves as the fitness function in the global optimization algorithm. The fitness function is reproducible and highly reliable, recalculated based on existing experience without relying on personal experience, and all calculation processes are recorded. This invention enables the light absorber to achieve extremely low average reflectance in the target wavelength band while also ensuring that the design parameters can be stably reproduced in the actual fabrication process.

[0023] 8. This invention provides a method for preparing a light absorber. In this embodiment, a polymer matrix is ​​dissolved in a mixed solvent to prepare a polymer matrix solution, providing an optically stable matrix solution for all subsequent sublayers. This ensures good adhesion between all interlayer interfaces and reduces the likelihood of interlayer delamination. This invention also modifies the surface of the oxide particles, forming an organic modification layer on the particle surface. This transforms the direct interaction between oxide particles into weak interactions between organic segments, inhibiting particle aggregation. This allows high-filling-content formulations (e.g., 68wt%-78wt% titanium dioxide) to remain stable without a sudden increase in viscosity or gelation. Furthermore, this invention decouples refractive index control from coating solution preparation—different refractive index sublayer coating solutions can be obtained by mixing the same dispersion in different proportions, avoiding the repetitive work of grinding and dispersing each layer from scratch. This method is suitable for mass production and offers high production efficiency.

[0024] 9. The present invention provides a method for preparing a light absorber, which involves surface modification of the oxide particles using a silane coupling agent and a phosphate dispersant. The silane coupling agent improves the interfacial compatibility between the oxide particles and the polymer matrix, while the phosphate groups form irreversible coordination bonds with the surface of the oxide particles, further reducing the interaction potential energy between particles. This composite modification scheme using a silane coupling agent and a phosphate dispersant solves the agglomeration problem of high-solids-content oxide particles in the polymer matrix from a chemical bonding perspective, enabling the oxide particles to maintain uniform dispersion even when the solid content reaches 68wt%-78wt% (corresponding to a volume fraction of 40vol%-45vol%).

[0025] 10. This invention also provides an application of a light absorber in photoelectric detection, imaging display, semiconductor devices, and precision optical systems. Because the light absorber of this invention achieves an average reflectivity of less than 0.5% in the target wavelength band (e.g., visible light band: 380nm-780nm), and employs a continuous dense thin-film structure with adhesion reaching ISO 2409 cross-cut adhesion Grade 1 (coating peel-off area less than 5%), it does not rely on free-supporting micro / nano structures and can be constructed on various material surfaces such as glass, silicon, metal, and flexible substrates. In the field of photoelectric detection, when used as a functional layer on the detector surface, the low reflectivity means less light is reflected and lost, increasing the effectively absorbed luminous flux and improving the detector's responsivity and sensitivity. In the field of imaging display, this invention can be used in the black matrix and optical anti-spurious structure of display devices; the light absorber attenuates incident ambient light within the absorption layer, resulting in a very low proportion of light reflected back to the observer, allowing the display panel to maintain high contrast even under strong ambient light. Simultaneously, its film layer is smooth and has low haze, not affecting the clarity of the displayed image. In the field of semiconductor devices, this invention utilizes light absorbers as device packaging layers or functional layers to reduce the impact of stray reflections on photolithography accuracy. It can also be used in optoelectronic devices such as solar cells to improve optical coupling efficiency. Furthermore, the all-wet process is compatible with the low-temperature requirements of semiconductors, preventing thermal damage to the completed device structure. In the field of precision optical systems, this invention leverages its high absorption characteristics to absorb stray light and suppress multiple reflections, thereby improving the system's stray light suppression ratio and imaging contrast. Its low-reflection characteristics covering a wide wavelength range also make this invention suitable for optical systems requiring broadband extinction. Attached Figure Description

[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0027] Figure 1 This is a schematic diagram of a light absorber structure provided in the first embodiment of the present invention.

[0028] Figure 2 This is a schematic diagram of another light absorber structure provided in the first embodiment of the present invention.

[0029] Figure 3 This is a schematic flowchart of a method for preparing a light absorber provided in the second embodiment of the present invention.

[0030] Figure 4 This is a detailed flowchart of step A of a method for preparing a light absorber provided in the second embodiment of the present invention.

[0031] Figure 5 This is a detailed flowchart of step A1 of a method for preparing a light absorber provided in the second embodiment of the present invention.

[0032] Figure 6 This is a detailed flowchart of step B of a method for preparing a light absorber provided in the second embodiment of the present invention.

[0033] Figure 7 This is a detailed flowchart of step B1 of a method for preparing a light absorber provided in the second embodiment of the present invention.

[0034] Figure 8 This is a detailed flowchart of step B2 of a method for preparing a light absorber provided in the second embodiment of the present invention.

[0035] Figure 9 This is a schematic flowchart of another method for preparing a light absorber provided in the second embodiment of the present invention.

[0036] Explanation of reference numerals in the attached diagram: 1. Absorbing layer; 2. Antireflective layer; 4. Air; 5. Substrate 10. Absorbing layer; 20. Antireflective layer; 30. Outer layer; 40. Air; 50. Substrate; 21. First sublayer; 22. Second sublayer. Detailed Implementation

[0037] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0038] In the embodiments provided by this invention, it should be understood that "B corresponding to A" means that B is associated with A, and B can be determined based on A. However, it should also be understood that determining B based on A does not mean determining B solely based on A; B can also be determined based on A and / or other information.

[0039] It should be understood that the phrase "one embodiment" or "an embodiment" throughout the specification means that a specific feature, structure, or characteristic related to the embodiment is included in at least one embodiment of the invention. Therefore, "in one embodiment" or "in an embodiment" appearing throughout the specification does not necessarily refer to the same embodiment. Furthermore, these specific features, structures, or characteristics can be combined in any suitable manner in one or more embodiments. Those skilled in the art should also recognize that the embodiments described in the specification are optional embodiments, and the actions and modules involved are not necessarily essential to the invention.

[0040] In various embodiments of the present invention, it should be understood that the sequence number of each process does not necessarily imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.

[0041] Please see Figure 1 The first embodiment of the present invention provides a light absorber, including an absorption layer 1 and an antireflection layer 2 disposed on the surface of the absorption layer; the absorption layer is composed of a polymer matrix and nano-absorbing units; the refractive index of the absorption layer is 1.48-1.55; the antireflection layer 2 includes at least two sub-layers stacked sequentially; the sub-layers are composed of a polymer matrix and oxide particles, and each sub-layer has a different refractive index by designing different types and / or mass fractions of oxide particles, and the refractive index of each sub-layer varies in a gradient direction in the stacking direction; the refractive index of each sub-layer is 1.20-1.91.

[0042] It is understandable that in traditional solutions, the extinction coefficient of the material and the impedance matching condition are mutually restrictive. Adjusting the light absorption capacity often compromises the anti-reflection effect of the material, making it difficult to simultaneously achieve impedance matching and multiple scattering absorption performance. This invention decouples these components into two functionally separate parts: absorption layer 1 is used to achieve efficient dissipation of incident light energy, and anti-reflection layer 2 is used to control the interface optical impedance matching relationship. The optical dissipation capability of absorption layer 1 is independently determined by the type, particle size, and concentration of its own absorbing units, and is independent of the optical admittance matching condition of the anti-reflection layer (i.e., it is not constrained by the refractive index and thickness conditions required for the anti-reflection layer to suppress interface reflection). On the other hand, the anti-reflection bandwidth of anti-reflection layer 2 (the wavelength range within which the anti-reflection layer can achieve effective anti-reflection) is independently determined by the refractive index and thickness of each sublayer, and is independent of the material system of absorption layer 1. This structure of this invention allows absorption layer 1 and anti-reflection layer 2 to be independently optimized for their respective functional objectives without requiring a performance trade-off between them.

[0043] It is understood that the absorption layer 1 is composed of a polymer matrix and nano-absorbing units. Specifically, the absorption layer 1 uses an optically transparent or semi-transparent polymer matrix as the continuous phase, and introduces nano-absorbing units with high extinction coefficients, such as carbon nanoparticles, metal oxide nanoparticles, or near-infrared absorbing dye composite particles, to form a composite system. The refractive index of the absorption layer 1 is determined by the intrinsic refractive index of the polymer matrix and the dispersion state, spatial distribution, and volume fraction of the nano-absorbing units. For example, when polyacrylate is used as the polymer matrix, its intrinsic refractive index is approximately 1.48-1.52. After introducing an appropriate amount of nano-absorbing units, based on the MG model, the equivalent refractive index of the composite film increases slightly but remains within the range of 1.48-1.55. This embodiment of the invention limits the refractive index of the absorption layer 1 to 1.48-1.55. This refractive index range ensures that the absorption layer 1 has sufficient optical density to achieve effective light energy dissipation, and also provides a reasonable boundary condition for the target refractive index of the sublayer of the antireflection layer 2 closest to the absorption layer 1. If the refractive index of the absorption layer 1 is too low, the antireflection layer 2 needs to start with an even lower refractive index, which increases the number of sublayers and the required film thickness; if the refractive index is too high, the reflectivity of the absorption layer 1 increases, which weakens the matching effect of the antireflection layer 2.

[0044] It can be understood that the antireflection layer 2 comprises multiple sublayers stacked sequentially. Each sublayer is composed of a polymer matrix and oxide particles. By designing different types and / or mass fractions of oxide particles, each sublayer has a different refractive index. The refractive index of each sublayer changes in a gradient along the stacking direction, which can eliminate Fresnel reflection caused by a sudden change in refractive index at the interface between air and the absorption layer. Fresnel reflection refers to the phenomenon that when light passes through the interface of two media with different refractive indices, a portion of the light is reflected back to the original medium due to the difference in refractive indices on both sides.

[0045] It is understandable that, from an optical principle perspective, when light travels from one medium to another, if the refractive indices of the two media differ, Fresnel reflection will occur at the interface. The refractive index of air is approximately 1.00, while the refractive index of the absorption layer in this embodiment is 1.48-1.55, resulting in a refractive index difference of 0.48-0.55. The corresponding single-interface Fresnel reflectance is approximately 4%-5%. This embodiment addresses this by setting an antireflection layer 2 on the surface of the absorption layer 1. The antireflection layer 2 comprises multiple sub-layers stacked sequentially. By utilizing these sub-layers with different refractive indices to construct a refractive index gradient in the thickness direction, a smooth transition of optical impedance is achieved between air and the absorption layer. The refractive indices of each sub-layer are 1.20-1.91, covering a range from a low value close to the refractive index of air (1.20) to a high value close to the refractive index of oxide particles (1.91), providing ample adjustment space for constructing a refractive index gradient from air to the absorption layer.

[0046] As an optional embodiment, the polymer matrix includes at least one of polyacrylate, polyurethane, or epoxy resin. It is understood that polyacrylate has good optical transparency, excellent film-forming properties, and controllable crosslinking density; its side-chain hydroxyl groups can undergo addition polymerization with the isocyanate curing agent to form a polyurethane crosslinking network. The polyurethane system has high toughness and abrasion resistance; the epoxy resin system has high adhesion and low curing shrinkage. The refractive indices of polyacrylate, polyurethane, or epoxy resin are all in the range of 1.48-1.52, and can simultaneously serve as the continuous phase of the absorber layer 1 and the antireflection layer 2 in the embodiments of the present invention.

[0047] As an optional implementation, the nano-absorbing unit can be one or more combinations of carbon black nanoparticles, carbon nanotube nanoparticles, graphene derivative nanoparticles, Fe3O4 nanoparticles, and MnO2 nanoparticles; the average particle size of the nano-absorbing unit is preferably 10nm-50nm, and the polydispersity index (PDI) of the particle size distribution is not higher than 0.15 to ensure the uniform dispersion of particles in the matrix. It is understood that carbon black nanoparticles have extremely high light absorption coefficients and broad-spectrum absorption characteristics, making them one of the most commonly used nano-absorbing materials in the visible light band; carbon nanotubes and graphene derivatives also have broad-spectrum absorption capabilities, but their dispersion is relatively difficult; metal oxide nanoparticles such as Fe3O4 and MnO2 have absorption characteristics in the visible to near-infrared bands. The average particle size of the nano-absorbing unit is selected to be 10nm-50nm, which is much smaller than the wavelength of visible light (380nm-780nm). This ensures that the particles are uniformly dispersed in the matrix without significant Mie scattering loss (i.e., scattering that occurs when light encounters particles with a size similar to its own wavelength), thus maintaining the bulk absorption characteristics of the absorption layer.

[0048] Continue as Figure 1 As shown in the diagram, as an optional implementation, the antireflective layer 2 includes at least two sublayers, corresponding to a first sublayer 21 and a second sublayer 22, respectively. The first sublayer 21 is disposed close to the absorption layer 1, and the second sublayer 22 is disposed close to the air side. Figure 1 As shown, a structure is formed by stacking a second sublayer 22, a first sublayer 21, and an absorption layer 1.

[0049] As an optional implementation, the oxide particles constituting the first sublayer 21 and the second sublayer 22 include at least one of titanium dioxide, zirconium oxide, niobium oxide, and hollow silica. It is understood that titanium dioxide (rutile type, refractive index approximately 2.5-2.7) is one of the most stable oxides with the highest refractive index and is suitable as a refractive index adjusting component for high-refractive-index sublayers. Zirconium oxide (refractive index approximately 2.0-2.2) and niobium oxide (refractive index approximately 2.1-2.5) can be used as alternatives to or supplements to titanium dioxide. Hollow silica refers to hollow silica nanospheres whose internal cavities are filled with air; the equivalent refractive index of a single hollow silica nanosphere can be as low as 1.10-1.30, making it suitable as a refractive index adjusting component for low-refractive-index sublayers. By selecting different types and / or mass fractions of oxide particles in different sublayers, the refractive index of each sublayer can be continuously controlled within the range of 1.20-1.91.

[0050] In another embodiment, the first embodiment of the present invention provides a light absorber, which further includes an outer layer; the outer layer is disposed on the side of the antireflection layer away from the absorption layer; the outer layer is a MgF2 thin film.

[0051] It is understandable that the refractive index of MgF2 thin films is approximately 1.38, which is relatively low among all stable dielectric thin films. Placing the MgF2 thin film on the side of the antireflection layer away from the absorption layer (i.e., the air-near side) can significantly reduce Fresnel reflection at the air-antireflection interface. Compared to using a nanoporous structure as the outermost low-refractive-index layer, the dense MgF2 thin film is free of pores and defects, exhibiting superior mechanical strength and abrasion resistance, thus avoiding performance losses caused by pore collapse or moisture absorption during use of porous structures.

[0052] In another implementation, please refer to Figure 2 The first embodiment of the present invention provides a light absorber, comprising an absorption layer 10, a first sublayer 21, a second sublayer 22, and an outer layer 30 stacked sequentially; the absorption layer 10 is a composite film incorporating carbon black nanoparticles, the thickness of the absorption layer 10 is 300nm-800nm, and in the optical wavelength range of 380nm-780nm, the real part of the equivalent complex refractive index is 1.48-1.55, and the imaginary part is 0.002-0.01; specifically, the equivalent complex refractive index A=n+ik, where n represents the real part, i represents the imaginary unit, which does not represent absorption or refraction itself, and k is the imaginary part (i.e., the extinction coefficient).

[0053] Continue reading Figure 2The first sublayer 21 is a composite film incorporating titanium dioxide, wherein the average particle size of the titanium dioxide is 10nm-20nm and the mass fraction is 30wt%-40wt%; the thickness of the first sublayer 21 is 70nm-80nm, and the refractive index is 1.60-1.64 in the optical wavelength range of 380nm-780nm; the second sublayer 22 is a composite film incorporating titanium dioxide, wherein the average particle size of the titanium dioxide is 10nm-20nm and the mass fraction is 68wt%-78wt%; the thickness of the second sublayer 22 is 125nm-145nm, and the refractive index is 1.89-1.91 in the optical wavelength range of 380nm-780nm; the outer layer 30 is a MgF2 film, the thickness of the outer layer 30 is 80nm-110nm, and the refractive index is 1.38 in the optical wavelength range of 380nm-780nm. The refractive index mentioned refers to the refractive index with λ=550 nm.

[0054] It can be understood that the four-layer structure, from the substrate side to the air side, is as follows: absorption layer 10 → first sub-layer 21 → second sub-layer 22 → outer layer 30. The corresponding equivalent refractive index distribution is: absorption layer (1.52) → first sub-layer (1.62) → second sub-layer (1.91) → outer layer (1.38), exhibiting a non-monotonic refractive index gradient change. From the perspective of optical principles, the core function of the antireflection layer is to smoothly transition the optical admittance between the air and the absorption layer along the film thickness direction to suppress Fresnel reflection at each interface. The Fresnel reflection intensity at each interface depends on the difference in refractive index between the two sides of the interface. In the structure of this embodiment, the high-refractive-index second sub-layer (1.91) and the lower-refractive-index first sub-layer (1.62) and outer layer (1.38) on both sides form two interfaces with a large refractive index difference. The reflected waves generated by the incident light at these interfaces have a phase difference due to the different propagation optical paths. This non-monotonic refractive index gradient stack, through the coordinated thickness design of the first sublayer, the second sublayer, and the outer layer, ensures that reflected waves from different interfaces at different wavelengths satisfy the destructive interference condition and cancel each other out in the 380nm-780nm visible light band. Simultaneously, the refractive index of the outer layer (1.38) is close to that of air (1.00), further mitigating the abrupt change in refractive index at the air-coating interface. Compared to existing technologies (two-stage discrete refractive index periodic stacking + transparent terminal), the non-monotonic distribution provides additional design freedom for phase matching of reflected waves from each interface, maintaining approximately anti-phase superposition of reflected waves over a wider wavelength range, thus achieving a larger anti-reflection bandwidth and a lower minimum reflectivity.

[0055] It is understandable that for the absorption layer 10, carbon black nanoparticles have a high extinction coefficient in the visible light band. After introducing them into the polyacrylate matrix at an appropriate volume fraction, the equivalent complex refractive index of the composite film is 1.52 + i0.005, where the real part 1.52 provides a boundary refractive index that matches the antireflection layer, and the imaginary part 0.005 represents a moderate light energy dissipation capability. The thickness of the absorption layer 10 is selected as 300nm-800nm ​​to ensure sufficient absorption path length for the incident light energy to be fully dissipated within the film layer, while avoiding excessive thickness that would increase internal stress and reduce adhesion.

[0056] It is understandable that the first sub-layer 21 plays a role in the refractive index transition between the absorption layer 10 and the second sub-layer 22. The refractive index of the first sub-layer 21 (1.62) is between the refractive index of the absorption layer 10 (1.52) and the refractive index of the second sub-layer 22 (1.91), thus playing a role in smoothing the refractive index transition.

[0057] It is understandable that the second sublayer 22 is the sublayer with the highest refractive index in the entire antireflective layer 20, with an equivalent refractive index of approximately 1.91 corresponding to a titanium dioxide mass fraction of 68wt%-78wt%. This high-refractive-index sublayer provides the greatest optical interference modulation capability.

[0058] It is understood that the refractive index of the outer layer 30, 1.38, is between the refractive index of air (1.00) and the refractive index of the second sublayer (1.91). As the outermost low-refractive-index layer, it reduces reflection loss at the air-coating interface. The MgF2 thin film can be deposited using radio frequency magnetron sputtering, and the film thickness is monitored in real time by a quartz crystal microbalance, achieving sub-nanometer thickness accuracy. The thickness of the outer layer 30, 80nm-110nm, works in conjunction with the thicknesses of the first sublayer 21 and the second sublayer 22 to satisfy the interference phase-matching condition in the 380nm-780nm wavelength band. In addition to having a low refractive index, the refractive index of the MgF2 thin film varies very little with wavelength in the visible to near-infrared band, and it has low dispersion. This means that it can stably perform anti-reflection effects throughout the entire visible light band, without exhibiting good anti-reflection effects at some wavelengths while increasing reflection at others. Furthermore, MgF2 films exhibit good chemical stability, resisting moisture and moderately acidic / alkaline environments. As the outermost layer, they can protect the internal polymer composite film from environmental corrosion, improving the long-term reliability of the device. Compared to polymer films, MgF2 films have higher mechanical hardness, which improves the scratch resistance of the outermost surface.

[0059] The light absorber of this invention achieves optical performance of an average reflectivity of 0.43% and a minimum reflectivity of 0.16%@642nm in the visible light band of 380nm-780nm through a functional separation structure design of the absorption layer 10, the antireflection layer 20 (including: a first sub-layer 21 and a second sub-layer 22) and the outer layer 30, and a non-monotonic refractive index gradient profile. At the same time, the continuous dense thin film structure ensures mechanical stability, making it suitable for applications such as photoelectric detection, imaging display, semiconductor devices and precision optical systems.

[0060] like Figure 3 As shown, the second embodiment of the present invention provides a method for preparing a light absorber, used to prepare the light absorber provided in the first embodiment of the present invention, comprising the following steps: Step A: Prepare the absorbent layer on the substrate using a wet process; Step B: Prepare an antireflection layer on the absorber layer using a wet process.

[0061] It is understood that both the absorption layer and the antireflection layer in the embodiments of the present invention can be realized by wet processing. Unlike the existing technology where high refractive index films must be deposited by PVD / CVD vacuum deposition, wet processing supports continuous production, can form films at normal pressure and low temperature, and has low equipment investment and low energy consumption. Moreover, the light absorber obtained by the preparation method provided in the second embodiment of the present invention has the same beneficial effects, that is, through the functional separation design of the absorption layer and the antireflection layer, the absorption layer can achieve efficient absorption of incident light in the 380nm–780nm light band, while the antireflection layer minimizes the reflection loss at the interface of each layer through the gradient refractive index structure, thereby obtaining an average reflectivity of less than 1% in the entire visible light band; the refractive index of each sub-layer in the antireflection layer changes gradient along the stacking direction, making the optical impedance transition between the refractive index of the absorption layer (1.48–1.55) and the air refractive index (1.0) tend to be smooth, widening the antireflection bandwidth, and avoiding the problem that the single-layer antireflection structure is only effective in the narrow band and the reflectivity rises rapidly in the edge band. Furthermore, since each sublayer is composed of a polymer matrix and oxide particles, the refractive index of each sublayer can be flexibly controlled by adjusting the type and / or mass fraction of the oxide particles. This allows the refractive index profile of the antireflective layer to be customized for the wavelength requirements of different applications without fundamentally changing the equipment or material system. Moreover, this embodiment employs a wet process, without relying on PVD or CVD vacuum deposition. The advantages of the all-wet process include: (1) Each layer of film is formed under normal pressure and low temperature conditions, and the substrate does not need to bear high temperature heat load, so that the method can be directly applied to flexible substrates (such as PET, PEN) and temperature-sensitive device structures; (2) Wet coating processes (spin coating, scraping coating, slot coating, spraying, etc.) support roll-to-roll continuous production, and the single batch capacity is much higher than that of intermittent vacuum coating. The equipment investment and operating energy consumption are significantly reduced, which is conducive to large-scale manufacturing and cost control; (3) The refractive index of each sub-layer can be precisely controlled by adjusting the type and mass fraction of oxide particles. There is no need to change the deposition source or adjust the vacuum process parameters. The process flexibility and repeatability are better than the all-dry deposition of traditional multilayer dielectric films.

[0062] As an optional implementation method, such as Figure 4 As shown, the absorber layer is prepared using a wet process, specifically including the following steps: Step A1: Mix the nano-absorbing units with the polymer matrix to obtain the absorption layer mixture; Step A2: Add a curing agent to the absorbent layer mixture and mix thoroughly to obtain an absorbent layer coating liquid with a dynamic viscosity of 50 mPa·s-500 mPa·s; and Step A3: Apply the absorbent coating liquid to the surface of the substrate and cure it to form the absorbent layer.

[0063] It is understandable that the function of the absorption layer is to convert incident light that passes through the antireflection layer into heat or other forms of energy. Its core lies in the uniform dispersion of the nano-absorbing units within the polymer matrix and the compatibility between the two. In step A1, the nano-absorbing units exist in a dispersed state within the polymer matrix, without chemical reaction. The nano-absorbing units provide light absorption, while the polymer matrix provides the film-forming framework and load-bearing capacity. In step A2, the addition of the curing agent transforms the polymer matrix from a flowable linear or low-crosslinked state into a crosslinkable curable reactive system. The curing agent reacts with reactive functional groups (such as hydroxyl groups) on the polymer matrix to form a crosslinked network, endowing the absorption layer with mechanical strength and solvent resistance. Controlling the dynamic viscosity within the range of 50 mPa·s to 500 mPa·s precisely balances the leveling requirements of the coating process with the requirement for uniform film thickness after deposition, enabling the absorption layer to achieve stable film quality within the designed thickness range of 300 nm to 800 nm. In step A3, after the coating liquid is applied to the substrate surface, the crosslinking reaction is completed through curing. The solvent in the wet film gradually evaporates, and the polymer network shrinks to form a film.

[0064] As an optional implementation, the nano-absorbing unit can be selected from at least one of carbon black nanoparticles, carbon nanotubes, graphene or graphene oxide derivatives, metal oxide nanoparticles, and metal nanoparticles. It is understood that different types of nano-absorbing units have different focuses in terms of light absorption mechanisms. Carbon black nanoparticles exhibit broad-spectrum, flat absorption characteristics in the visible light spectrum, with almost no drastic fluctuations with wavelength. They are low-cost, widely available, and among the most suitable materials for constructing broad-spectrum absorption layers. Carbon nanotubes and graphene derivatives achieve continuous absorption from the ultraviolet to the near-infrared spectrum through intraband transitions in the sp² carbon skeleton. They also possess high specific surface area and thermal conductivity, which facilitates the rapid dissipation of heat generated during absorption and avoids localized overheating. However, their dispersion in polymer matrices is slightly more difficult than that of carbon black nanoparticles, and they usually require surface functionalization treatment. Metal oxide nanoparticles (such as iron(III) oxide and copper oxide) have relatively concentrated absorption bands, but their absorption peak positions can be shifted within the visible light band by controlling particle size and morphology, making them suitable for light absorbers that require absorption at specific wavelengths. Gold, silver, and other metal nanoparticles rely on localized surface plasmon resonance absorption, exhibiting extremely strong absorption cross-sections at the resonance wavelength. However, their absorption bandwidth is relatively narrow, and multiple particle size combinations are usually required to cover the entire visible light band, and the raw material costs are relatively high. Considering the comprehensive advantages of carbon black nanoparticles in terms of broad-spectrum absorption characteristics, dispersibility, and cost, carbon black nanoparticles are preferably used as the nano-absorbing unit in the embodiments of the present invention. Those skilled in the art will understand that the selection of the nano-absorbing unit does not constitute a limitation of the present invention, as long as it can achieve the function of the absorption layer described in the embodiments of the present invention. Accordingly, when selecting different types of nano-absorbing units, their surface functionalization treatment methods and dispersion process parameters (such as centrifugal mixing speed, ultrasonic crushing power, and time) can be adaptively adjusted according to the surface chemical characteristics of the nano-absorbing unit. For example, carboxyl groups can be preferentially introduced into carbon nanotubes to enhance their compatibility with the polymer matrix, and silane coupling agents can be preferentially used to modify metal oxide nanoparticles to improve interfacial bonding.

[0065] As an optional implementation, the nano-absorbing units account for 0.5 wt%-10 wt% of the total mass of the absorption layer mixture. The mass fraction of the nano-absorbing units directly affects the extinction coefficient and film quality of the absorption layer. When the mass fraction is below 0.5 wt%, the extinction coefficient is insufficient, making it difficult to achieve effective light dissipation; when the mass fraction is above 10 wt%, the particle solid content is too high, which easily leads to agglomeration, resulting in increased film roughness and unacceptable scattering loss. The range of 0.5 wt%-10 wt% maintains good film quality while ensuring a sufficient extinction coefficient.

[0066] As an optional implementation, in step A2, the curing agent may be a polyisocyanate (e.g., hexamethylene diisocyanate, HDI). The hydroxyl groups on the side chains of the polymer matrix can undergo addition polymerization with the isocyanate groups under heating conditions to form a urethane crosslinking network. Further, the molar ratio of isocyanate groups to hydroxyl groups is controlled at 1.0-1.2 to ensure sufficient reaction and no excess free isocyanate residue.

[0067] As an optional implementation, in step A3, the absorption layer can be coated using one of the following methods: spin coating, blade coating, slot coating, and spray coating. Different viscosity ranges are preferred for different coating methods: spin coating preferably 50 mPa·s-150 mPa·s, blade coating preferably 100 mPa·s-300 mPa·s, slot coating preferably 50 mPa·s-200 mPa·s, and spray coating preferably 50 mPa·s-100 mPa·s. If the viscosity of the absorption layer coating liquid is insufficient, the leveling properties of the absorption layer coating liquid on the substrate surface will be poor, making it difficult to form a uniform and continuous film; if the viscosity of the absorption layer coating liquid is too high, it will be difficult to control the dispersion of the nano-absorbing units. Precise control of viscosity ensures the leveling of the wet film on the substrate surface and the uniformity of film thickness.

[0068] As an optional implementation, in step A3, the absorbent layer coating liquid is applied to the surface of the substrate and cured to form the absorbent layer. The curing method can be either thermosetting or UV curing. If thermosetting is used: the curing conditions are 80℃-150℃ for 10-30 minutes, preferably 100℃-130℃; the advantages of thermosetting are controllable crosslinking density, low curing shrinkage, and excellent film toughness and adhesion. If UV curing is used: UV curing uses a photoinitiator instead of a thermosetting agent, initiating a free radical polymerization reaction of acrylate double bonds under ultraviolet light irradiation (wavelength 365nm, irradiation energy 100mJ / cm²-500mJ / cm²); the advantages of UV curing are fast curing speed, suitability for heat-sensitive substrates (such as PET film, heat distortion temperature approximately 120℃), low energy consumption, and prevention of substrate heat deformation. The thickness of the absorption layer obtained after curing in step A3 is 300nm-800nm, and the root mean square roughness of the film surface is no higher than 20nm, which is sufficient to ensure the interface optical matching accuracy between the subsequent antireflection layer and the absorption layer.

[0069] like Figure 5 As shown, as an optional implementation, to prevent the nano-absorbing units from agglomerating when mixed with the polymer matrix, step A1 further includes the following steps: Step A11: Dissolve the polymer matrix in a mixed solvent to prepare a polymer matrix solution; Step A12: Perform surface functionalization treatment on the nano-light-absorbing unit to form an organic modification layer containing reactive functional groups on the surface of the nano-light-absorbing unit; Step A13: Add the surface-functionalized nano-absorbing units to the mixed solvent, and after centrifugation, obtain the nano-absorbing unit premixed solution; Step A14: Place the premixed solution into an ultrasonic cell disruptor, and break up the nano-absorbing unit aggregates using a jet stream to achieve primary particle dispersion, obtaining a nano-absorbing unit dispersion; and Step A15: Add the nano-absorbing unit dispersion to the polymer matrix solution and mix to obtain the absorption layer mixture.

[0070] It is understandable that, from the perspective of dispersion mechanism analysis, nano-absorbing units, due to their large specific surface area and high surface energy, are prone to secondary aggregation in solution due to van der Waals forces and electrostatic attraction. In this embodiment of the invention, the nano-absorbing units are first subjected to surface functionalization treatment, then centrifugation pre-dispersion, and finally ultrasonic fine dispersion. That is, a three-stage combined process of "surface functionalization treatment + centrifugation pre-dispersion + ultrasonic fine dispersion" is used to achieve primary particle-level dispersion of the nano-absorbing units.

[0071] As an optional implementation, the solid content of the polymer matrix in step A11 is 15wt%-30wt% of the total solution. If the solid content is too low, the viscosity of the coating solution is insufficient, resulting in poor leveling of the wet film on the substrate surface and making it difficult to form a uniform and continuous film; if the solid content is too high, the solution viscosity is too high, which is not conducive to the dispersion of nanoparticles and subsequent mixing operations. In this embodiment of the invention, the polymer matrix solid content range of 15wt%-30wt% provides a suitable viscosity environment for the uniform dispersion of the nano-absorbing units.

[0072] As an optional implementation, the mixed solvent is mainly composed of butyl acetate and ethyl acetate (the two together account for more than 70% of the total solvent mass), supplemented with a small amount of methyl ethyl ketone (MEK, accounting for 5%-15% of the total solvent mass) to adjust the evaporation rate, and toluene (accounting for 5%-10% of the total solvent mass) can be added to improve the resin solubility and leveling properties.

[0073] As an optional implementation, the surface functionalization treatment in step A12 is used to introduce an organic modification layer containing reactive functional groups on the surface of the nano-absorbing unit. Specifically, the reactive functional groups are selected from at least one of carbon-carbon double bonds, carboxyl groups, hydroxyl groups, and silanol groups. Specifically, carbon-carbon double bonds can participate in the free radical crosslinking reaction of the polymer matrix, achieving covalent bonding between the nano-absorbing unit and the polymer matrix network, thus improving the mechanical integrity and long-term stability of the composite film. Carboxyl and hydroxyl groups can enhance the hydrogen bonding interaction between the nano-absorbing unit and the polymer matrix, improving interfacial compatibility. Silanol groups can undergo condensation reactions with reactive groups in the polymer matrix to form covalent bonds. The role of surface functionalization is to: reduce the surface energy of the nanoparticles, inhibiting van der Waals-driven secondary aggregation; enhance the interfacial compatibility between the nanoparticles and the polymer matrix, avoiding phase separation and precipitation of particles during film formation; and achieve covalent bonding between the nanoparticles and the polymer network by introducing functional groups that can participate in crosslinking reactions. Specifically, taking carbon black particles as the nano-absorbing unit as an example, surface modification is performed using organic sulfonates or carboxylates (grafting density 0.5 μmol / m²-2.5 μmol / m²); if the nano-absorbing unit is carbon nanotubes and graphene derivatives, mild acid oxidation treatment is used to introduce carboxyl and hydroxyl surface functional groups; if the nano-absorbing unit is Fe3O4 nanoparticles, oleic acid or 3-(trimethoxysilyl)propyl methacrylate (MPS) silane coupling agent is used for surface coating.

[0074] As an optional implementation, in step A13, after the surface-functionalized nano-absorbing units are added to the mixed solvent, air bubbles are removed by planetary centrifugation (2000 rpm, 2-3 min) or vacuum static degassing (-0.09 MPa, 15-30 min) to obtain a premixed solution. It can be understood that planetary centrifugation utilizes the high shear force generated by the combined revolution and rotation motion to achieve macroscopic dispersion of the nano-absorbing units and initial breakup of agglomerates. Adding the mixed solvent during centrifugation can regulate the evaporation rate and improve resin solubility and leveling properties.

[0075] As an optional implementation, in step A14, the premixed liquid is placed in an ultrasonic cell disruptor, where the nano-absorbing unit aggregates are broken up by jet propulsion to achieve a primary particle dispersion, resulting in a nano-absorbing unit dispersion. It can be understood that the ultrasonic cell disruptor utilizes the acoustic cavitation effect—an ultrasonic transducer generates high-frequency pressure waves in the liquid, causing the formation of micron-sized bubbles. Under the influence of the acoustic field, these bubbles expand, compress, and implode, collapsing instantly. The collapse generates high-temperature, high-pressure micro-jet propulsion and strong shear force locally, breaking the nano-absorbing unit aggregates down to the primary particle level. Further, achieving a primary particle dispersion means that the polydispersity index of the primary particle dispersion is no higher than 0.15. The lower the polydispersity index, the narrower the particle size distribution and the more uniform the optical properties of the composite film. This embodiment limits the polydispersity index to no higher than 0.15, ensuring the uniformity of the nano-absorbing unit size distribution.

[0076] As an optional implementation method, such as Figure 6 As shown, the antireflection layer is prepared using a wet process, specifically including the following steps: Step B1: Obtain the target refractive index and target thickness of each sublayer in the antireflection layer using TMM and global optimization algorithms; Step B2: Based on the target refractive index, mix the oxide particles with the polymer matrix, and obtain a multilayer coating solution by adjusting the type and / or mass fraction of the oxide particles; and Step B3: Based on the target thickness, coat and cure multiple sublayer coating liquids on the side of the absorption layer away from the substrate to construct multiple sublayers with different refractive indices, forming an antireflection layer composed of multiple sublayers.

[0077] It is understood that the embodiments of the present invention, when designing the antireflection layer, solve for a combination of refractive indices and thicknesses of a set of sublayers to ensure that the reflected light at each interface of the incident light in the multilayer film system cancels each other out as much as possible. When there are many sublayers and the refractive index profile is not monotonically changing, the correspondence between the reflection spectrum of the film system and the parameters of each layer is very complex and cannot be solved directly by simple analytical formulas. Traditional methods often rely on the designer's experience to try and match layer by layer. After adjusting the parameters of a certain layer, the phase matching relationship of other layers changes accordingly, resulting in slow convergence and easy stagnation at local extrema. In step B1, the target refractive index and target thickness of each sublayer in the antireflection layer are obtained through TMM and global optimization algorithms, which can find a near-globally optimal refractive index and thickness configuration within a given material system. In step B2, the target refractive index is converted into a coatable solution formulation. The refractive index of the sublayer is jointly determined by the refractive index of the polymer matrix and the refractive index of the oxide particles according to the mixing rule. When the refractive index of the oxide particles is higher or lower than that of the polymer matrix, the refractive index of the sublayer increases or decreases with the increase of particle content, respectively. Accordingly, by selecting different types of oxide particles and adjusting their mass fraction based on the target refractive index of each sublayer, the refractive index of each sublayer can be continuously controlled within a certain range. In step B3, based on the target thickness of each sublayer, the thickness of the wet film formed in each coating is controlled by coordinating coating parameters (such as spin coating speed and time, and scraping gap and speed) and the solid content of the coating liquid. Then, pre-baking and curing are performed to allow solvent evaporation and cross-linking reactions to complete, thus constructing multiple sublayers with different refractive indices layer by layer. Since each sublayer uses a polymer matrix as a continuous phase, and adjacent sublayers are transitioned by interwoven homologous polymer molecular chains, there is no chemical incompatibility between dissimilar materials at the interlayer interface, resulting in good interfacial adhesion and reducing the likelihood of interlayer delamination. Furthermore, the coating liquid for each sublayer can be prepared in batches in advance, resulting in high production efficiency.

[0078] As an optional implementation, the polymer matrix for preparing the antireflective layer is prepared using the same method as the polymer matrix for preparing the absorbent layer.

[0079] To obtain the optimal parameter combination for each sublayer in the antireflection layer, as an optional implementation method, refer to... Figure 7 Step B1 specifically includes the following steps: Step B11: Based on the parameter combinations of refractive index and thickness that can be fabricated for each sublayer, establish a candidate set; Step B12: Based on the MG model and the volume fraction φ_abs of the nano-absorbing units in the absorption layer, calculate the complex refractive index of the absorption layer and use the complex refractive index of the absorption layer as the terminal admittance. Step B13: Using the refractive index and thickness of each sublayer as design variables, construct an objective function with the goal of achieving the minimum average reflectivity R_avg in the 380nm-780nm band. Step B14: Calculate the spectral reflectance R(λ) of the parameter combination in the candidate set using TMM, and integrate to obtain the average reflectance, which is used as the fitness in the global optimization algorithm; Step B15: Use a global optimization algorithm to find the parameter combination that minimizes the reflection loss of the absorbed light; and Step B16: Based on process feasibility, the target refractive index and target thickness of each sublayer are obtained after screening.

[0080] Existing technologies employ the classic quarter-wavelength stacking theory when designing the refractive index and thickness of each sublayer, requiring the optical thickness of each layer to be an odd multiple of a quarter wavelength. However, this theory is only applicable to periodic high / low refractive index alternating stacks on transparent substrates and cannot be directly applied to light absorbers terminated by high extinction absorption layers. This invention employs the TMM (Transmission Matrix Method) to perform spectral calculations on arbitrary stacked structures and combines this with a global optimization algorithm to search for the optimal parameter combination in the parameter space.

[0081] As an optional implementation, in step B11, the candidate set is established based on the possible combinations of refractive index and thickness parameters for each sublayer, i.e., the possible combinations of refractive index and thickness parameters constitute the candidate set. It is understood that the refractive index range of each sublayer is determined by the available oxide particle type and polymer matrix. For example, when using polyacrylate as the polymer matrix: the equivalent refractive index of the hollow silica / polyacrylate composite system can be controlled within the range of 1.20-1.45, and the equivalent refractive index of the titanium dioxide / polyacrylate composite system can be controlled within the range of 1.50-1.90. Further, in this embodiment, the thickness range of each sublayer is set to 50nm-150nm, and the parameter settings can be discrete or continuous.

[0082] As an optional implementation, in step B12, the complex refractive index of the absorption layer is calculated based on the MG model, which is the Maxwell Garnett (MG) effective dielectric model. The MG model describes the relationship between the equivalent dielectric constant of the composite dielectric and the dielectric constants of each component and the volume fraction of the discrete phase.

[0083] in, The equivalent dielectric constant of the composite medium; The dielectric constant of the discrete phase; The permittivity is the constant of the continuous phase; The volume fraction of the discrete phase is denoted as . The equivalent complex refractive index can be derived from the equivalent dielectric constant, where the real part of the equivalent complex refractive index is the refractive index and the imaginary part is the extinction coefficient. The complex refractive index of the absorption layer is used as the boundary condition (terminal admittance) for the optical admittance matching calculation of the antireflection layer, ensuring that the optimization objective of the antireflection layer directly corresponds to the absorption layer. When the volume fraction of the nano-absorbing units in the absorption layer needs adjustment, the MG model can automatically update the complex refractive index of the absorption layer and recalculate the target parameters of each sublayer of the antireflection layer, achieving decoupled design between the absorption layer and the antireflection layer.

[0084] As an optional implementation, in step B13, the refractive index and thickness of each sublayer are used as design variables, with the goal of minimizing the average reflectance of the wavelength band to be absorbed. It can be understood that the average reflectance R_avg is defined as the integral average of the spectral reflectance R(λ) over the target wavelength band. Unlike the classic design method that optimizes reflectance at a single wavelength, minimizing the average reflectance allows the antireflection layer to achieve a balanced reflection suppression effect across the entire target wavelength band (e.g., 380nm-780nm), avoiding the problem of achieving extremely low reflectance at one wavelength but experiencing a rebound in reflectance at other wavelengths.

[0085] As an optional implementation, in steps B14 and B15, the spectral reflectance R(λ) of each parameter combination in the candidate set is calculated using the Transfer Matrix Method (TMM), and the average reflectance is obtained by integration as the fitness of the global optimization algorithm. The TMM transforms the propagation problem of incident light in a multilayer medium into matrix operations by establishing the characteristic matrices of each sublayer, allowing for rigorous calculation of the reflectance and transmittance of any stacked structure at any wavelength and incident angle. The global optimization algorithm performs global optimization in the parameter space using a swarm search strategy. Specifically, the global optimization algorithm can be a genetic algorithm or a particle swarm optimization algorithm. The genetic algorithm simulates natural selection and genetic mechanisms, searching for the optimal solution in a multi-generational population through selection, crossover, and mutation operations; the particle swarm optimization algorithm simulates the foraging behavior of bird flocks, searching guided by the historical best positions of individuals and the population. Both methods avoid the problem of getting trapped in local minima in a high-dimensional, multi-peak parameter space.

[0086] As an optional implementation, in step B16, the target refractive index and target thickness of each sublayer are determined from multiple candidate parameter combinations based on process feasibility. It is understood that the global optimization algorithm may output multiple candidate parameter combinations with similar performance, requiring selection based on process feasibility (such as the controllable range of film thickness accuracy, the feasibility of discrete refractive index values, and the risk of interlayer solvent miscibility).

[0087] As an optional implementation method, refer to Figure 8 Step B2 specifically includes the following steps: Step B21: Dissolve the polymer matrix in a mixed solvent to prepare a polymer matrix solution; Step B22: Perform surface modification on the oxide particles; Step B23: Add the surface-modified oxide particles to the mixed solvent, and after dispersion and mixing, obtain an oxide particle dispersion; and Step B24: Weigh the oxide particle dispersion according to the target refractive index, and mix the oxide particle dispersion with the polymer matrix to prepare multiple sublayer coating liquids that can construct sublayers with different refractive indices.

[0088] As an optional implementation, the mixed solvent used in step B21 is the same as the mixed solvent used in step A13.

[0089] As an optional implementation, in step B22, when modifying the surface of the oxide particles, a silane coupling agent and a phosphate dispersant are used to modify the surface of the oxide particles; the silanol groups in the silane coupling agent undergo a condensation reaction with the hydroxyl groups on the surface of the oxide particles to form covalent bonds; and the phosphate groups in the phosphate dispersant form coordination bonds with the surface of the oxide particles.

[0090] For example, the oxide particles are titanium dioxide, and the silane coupling agent is 3-(trimethoxysilyl)propyl methacrylate (MPS / TMSPM). The molecular structure of this silane coupling agent contains two key functional ends: one end is a hydrolyzable methoxysilyl group, which can hydrolyze in trace amounts to generate silanol groups (Si-OH). These silanol groups undergo a condensation reaction with the hydroxyl groups (Ti-OH) on the surface of the oxide particles, removing water molecules to form stable Ti-O-Si covalent bonds, anchoring the coupling agent molecules to the particle surface; the other end is a methacrylate group (C=C double bond), which can participate in the free radical crosslinking reaction of the polyacrylate resin, achieving covalent bonding between the oxide particles and the polymer network. Preferably, the grafting amount of the silane coupling agent is approximately 5wt%-10wt% of the oxide particle mass.

[0091] For example, the oxide particles are titanium dioxide, and the phosphate ester dispersant is a vinyl phosphate or methacrylate functional monomer. Preferably, the amount of the phosphate ester dispersant is 3wt%-5wt% of the oxide particle mass. The phosphate ester groups form irreversible coordination bonds with the surface of the oxide particles, providing a steric stabilization effect and further reducing the interaction potential energy between particles.

[0092] The composite modification scheme of silane coupling agent and phosphate ester dispersant solves the problem of agglomeration of high solid content oxide particles in polymer matrix from the chemical bonding level. It enables the oxide particles to maintain uniform dispersion even when the solid content reaches 68wt%-78wt% (corresponding to a volume fraction of 40vol%-45vol%), thus providing a basic support for the wet process to prepare a film with a refractive index of 1.91 in the embodiments of the present invention.

[0093] In step B23, the surface-modified oxide particles are added to the mixed solvent and ultrasonically dispersed for 10-20 minutes to obtain an oxide particle dispersion. It can be understood that the dispersion and mixing employs a combination of planetary centrifugal mixing and ultrasonic dispersion, with process parameters similar to those used in the dispersion of the nano-absorbing units in the absorption layer. The concentration and stability of the oxide particle dispersion directly affect the preparation accuracy and film quality of the sublayer coating solution. Preferably, the solid content of the oxide particle dispersion is controlled within the range of 40wt%-60wt%. The concentration of the dispersion directly affects the preparation accuracy of the sublayer coating solution: if the concentration is too low, the amount required to achieve the target refractive index increases, and the amount of solvent introduced increases, which dilutes the polymer matrix and reduces the viscosity of the coating solution, causing the wet film thickness to deviate from the design value; if the concentration is too high, the interparticle spacing decreases, the interparticle interaction increases, and the dispersion is prone to gelation or sedimentation. The stability of the dispersion determines its uniformity within the usage window: if the dispersion settles or agglomerates after preparation, the actual solid content of the same dispersion will fluctuate when sampled at different times, leading to deviations in the refractive index of the sublayer coating solution, ultimately causing the film refractive index to deviate from the target value and reducing the consistency of the film's optical properties. Therefore, this embodiment ensures the dispersion remains uniform and stable before coating by controlling the solid content of the dispersion and combining planetary centrifugal mixing with ultrasonic dispersion, thereby ensuring the preparation accuracy of the sublayer coating solution and the quality of the film.

[0094] In step B24, based on the target refractive index, the oxide particle dispersion is weighed and mixed with the polymer matrix to prepare multiple sublayer coating solutions capable of constructing sublayers with different refractive indices. It can be understood that different sublayers have different target refractive indices, corresponding to different types / mass fractions of oxide particles. For example, if the target refractive index of the first sublayer is 1.62, then the oxide particles should be 30wt%-40wt% titanium dioxide; if the target refractive index of the second sublayer is 1.91, then the oxide particles should be 68wt%-78wt% titanium dioxide. As an optional implementation, when preparing the sublayer coating solution, the oxide particle dispersion is weighed and prepared according to calculations using the MG model. After mixing the oxide particle dispersion with the polymer matrix solution, a curing agent is added, and the mixture is filtered through a 0.45-micron pore size PTFE filter to remove bubbles, thus obtaining the sublayer coating solution.

[0095] As an optional implementation, in step B3, multiple sublayer coating solutions are coated and cured on the side of the absorber layer away from the substrate according to the target thickness. It is understood that each sublayer is sequentially coated onto the absorber layer surface according to a designed stacking order. After each sublayer is coated, it undergoes low-temperature pre-curing (80℃-100℃, 5min-10min) to fix the refractive index of that sublayer, preventing interlayer solvent missolution and damage to the interlayer interface during subsequent coating processes. Further, UV curing can be used to achieve cross-linking after pre-curing. After each sublayer is coated and cured, the actual thickness and refractive index of that sublayer can be measured online using a spectroscopic ellipsometry. When the deviation exceeds a preset threshold (thickness deviation exceeding ±3% or refractive index deviation exceeding ±0.02), automatic or manual feedback correction is performed: the refractive index deviation is corrected by adjusting the oxide particle concentration in the next sublayer coating solution, or a compensation amount is introduced into the target thickness of the next sublayer to minimize the cumulative deviation of the total optical thickness. This feedback correction can instantly compensate for the inherent film thickness fluctuations in wet coating, controlling the thickness deviation of each functional layer within ±3%.

[0096] like Figure 9 As shown, in another embodiment, the method for preparing the light absorber includes the following steps: Step A': Prepare the absorbent layer on the substrate using a wet process; Step B': Prepare an antireflection layer on the absorber layer using a wet process; Step C': Prepare the outer layer on the antireflection layer.

[0097] As an optional implementation, the outer layer is a MgF2 thin film; that is, in this embodiment of the invention, an additional MgF2 thin film is prepared on the antireflection layer. To obtain higher film thickness accuracy, the MgF2 thin film can be prepared using a dry deposition process. The dry deposition process can be radio frequency magnetron sputtering deposition, plasma-enhanced chemical vapor deposition (PECVD), or electron beam evaporation deposition. Taking radio frequency magnetron sputtering as an example, in the specific preparation of the MgF2 thin film: a high-purity MgF2 target is used as the sputtering target, and the base vacuum degree is better than 5 × 10⁻⁶. -4 Pa, Ar flow rate 20sccm-40sccm, working pressure 0.5Pa-1.0Pa, RF power 100W-200W, deposition rate 0.1nm / s-0.5nm / s, and film thickness monitored in real time by a quartz crystal microbalance.

[0098] As an optional implementation, the outer layer is a composite film incorporating hollow silica nanospheres, wherein the average particle size of the silica nanospheres is 10nm-20nm and the mass fraction is 30wt%-40wt%; the thickness of the outer layer is 70nm-80nm, and the refractive index is 1.20 in the 380nm-780nm optical wavelength range; in this embodiment, the light absorber adopts a fully wet process. Compared with dry or wet-dry hybrid processes, wet processes require lower equipment investment and eliminate the need for vacuum procedures.

[0099] As an optional implementation, the preparation process of the composite film incorporating hollow silica nanospheres is the same as that of each sublayer in the antireflective layer, specifically including: dissolving the polymer matrix in a mixed solvent to prepare a polymer matrix solution; surface-modifying the hollow silica nanospheres to improve their interfacial compatibility with the polymer matrix; adding the surface-modified hollow silica nanospheres to the mixed solvent, and obtaining a hollow silica dispersion after planetary centrifugation and ultrasonic dispersion; weighing the hollow silica dispersion (hollow silica nanosphere mass fraction 30wt%-40wt%) according to the target refractive index of 1.20, mixing it with the polymer matrix solution, adding a curing agent, filtering and degassing to obtain an outer coating liquid; coating the outer coating liquid on the side of the antireflective layer opposite to the absorption layer, pre-curing and then curing to form an outer layer with a thickness of 70nm-80nm and a refractive index of 1.20. Unlike the aforementioned MgF2 thin film outer layer which uses dry deposition processes such as radio frequency magnetron sputtering, the hollow silica nanosphere outer layer is prepared using a wet coating process that is homologous to the antireflection layer sublayer. Thus, together with the absorption layer and the antireflection layer, it forms a fully wet process path, which can eliminate the vacuum process and reduce equipment investment.

[0100] The third embodiment of the present invention provides an application of any light absorber as described in the first embodiment in photoelectric detection, imaging display, semiconductor devices and precision optical systems.

[0101] It is understood that the light absorber claimed in this invention achieves an average reflectivity of 0.43% in the visible light band (380nm-780nm), while employing a continuous dense thin-film structure with adhesion reaching ISO 2409 cross-cut adhesion Grade 1 (coating peel-off area less than 5%). It does not rely on freely supportable micro / nano structures and can be constructed on various material surfaces such as glass, silicon, metal, and flexible substrates. In the field of photoelectric detection, this light absorber can be used for stray light removal on the inner wall of detectors and in optical paths, reducing background noise and improving the signal-to-noise ratio. In the field of imaging and display, it can be used for black substrates and optical stray light removal structures in display devices. In the field of semiconductor devices, it can be used for optical shielding and anti-interference coatings on device surfaces. In the field of precision optical systems, it can be used for light trapping, blackbody calibration, and instrument inner wall extinction.

[0102] To illustrate the technical effects of the embodiments of the present invention, the following experiments and performance tests were conducted: Experimental Example 1: This experimental example demonstrates the preparation of a light absorber according to the preparation method provided in the second embodiment of the present invention. The substrate used is a Corning Eagle XG glass slide, which was ultrasonically cleaned for 10 minutes each with detergent, acetone, and ethanol sequentially before use, and then dried with nitrogen. The structure of the light absorber in Experimental Example 1 is as follows: Substrate → Absorber layer (1.52) → First sublayer (1.80) → Second sublayer (1.55) → Third sublayer (1.28) The value in parentheses represents the measured refractive index of the layer at λ=550 nm.

[0103] The specific preparation steps for Example 1 are as follows: Step 1: Preparation of the absorbent layer: Polyacrylate resin (30wt% solid content, 100mg KOH / g hydroxyl value, number-average molecular weight Mn=10000) was dissolved in a mixed solvent (butyl acetate / ethyl acetate / methyl ethyl ketone mass ratio of 6:2:2) to prepare a polymer matrix solution with a solid content of 20wt%. Carbon black nanoparticles (average particle size 25nm) were surface-functionalized to introduce an organic modification layer containing carboxyl and hydroxyl groups onto the surface of the carbon black nanoparticles. The surface-functionalized carbon black nanoparticles were added to the mixed solvent and mixed by planetary centrifugation (2000rpm, 2min) to obtain a premix. The premix was placed in an ultrasonic cell disruptor and treated at 150W power, 24kHz frequency, pulse mode, 50% duty cycle for 10min to break up the carbon black nanoparticle aggregates through jet injection, achieving a primary particle dispersion state to obtain a carbon black nanoparticle dispersion with a polydispersity index of 0.12. A carbon black nanoparticle dispersion (carbon black nanoparticles accounting for 3 wt% of the total mass of the absorber layer mixture) was added to the polymer matrix solution and mixed by planetary centrifugation (2000 rpm, 3 min) to obtain the absorber layer mixture. HDI polyisocyanate curing agent (-NCO / -OH molar ratio of 1.1) was added to the absorber layer mixture and mixed thoroughly to obtain an absorber layer coating solution with a dynamic viscosity of 120 mPa·s. The absorber layer coating solution was filtered through a 0.45 μm pore size PTFE filter to remove bubbles, and then coated onto the surface of a glass slide using a doctor blade (100 μm gap, coating speed 20 mm / s). After heat curing at 100℃ for 20 min, an absorber layer with a thickness of 500 nm and an equivalent complex refractive index of 1.52 + i0.005 was formed.

[0104] Step 2: Obtain the target refractive index and target thickness of each sublayer: A candidate set is established based on parameter combinations of hollow silica / polymer (1.20-1.45) and titanium dioxide / polymer (1.50-1.90). Based on the MG model and the volume fraction of carbon black nanoparticles in the absorption layer (approximately 1.5 vol%), the complex refractive index of the absorption layer, 1.52 + i0.005, is calculated as the terminal admittance. Using the refractive index and thickness of each sublayer as design variables, an objective function is constructed with the optimization direction of minimizing the average reflectance from 380 nm to 780 nm. The spectral reflectance of the parameter combinations in the candidate set is calculated using TMM and integrated to obtain the average reflectance. A genetic algorithm is used for global optimization. After screening based on process feasibility, the target refractive index of the first sublayer is 1.80, and the target thickness is 75 nm; the target refractive index of the second sublayer is 1.55, and the target thickness is 128 nm; and the target refractive index of the third sublayer is 1.28, and the target thickness is 102 nm.

[0105] Step 3: Preparation of the sublayer coating solution: Polyacrylate resin is dissolved in a mixed solvent to prepare a polymer matrix solution. Titanium dioxide nanoparticles (rutile type, average particle size 15 nm) are surface-modified using a silane coupling agent (MPS, grafted at 8 wt% of titanium dioxide mass) and a phosphate dispersant (4 wt% of titanium dioxide mass). The silanol groups in the silane coupling agent condense with the hydroxyl groups on the titanium dioxide surface to form Ti-O-Si covalent bonds, and the phosphate groups in the phosphate dispersant form coordination bonds with the titanium dioxide surface. The surface-modified titanium dioxide is added to the mixed solvent, and after planetary centrifugation and ultrasonic dispersion, a titanium dioxide dispersion is obtained. Based on a target refractive index of 1.80, the titanium dioxide dispersion (58 wt% titanium dioxide mass fraction) is weighed and mixed with the polymer matrix solution. After adding HDI curing agent, the mixture is filtered and degassed to obtain the first sublayer coating solution. Based on a target refractive index of 1.55, a titanium dioxide dispersion (20 wt% titanium dioxide) was weighed and the second sub-layer coating solution was prepared using the same method. Based on a target refractive index of 1.28, a hollow silica dispersion (40 wt% hollow silica) was weighed and the third sub-layer coating solution was prepared using the same method.

[0106] Step 4: Coating and Curing Sublayers: The first sublayer coating solution is applied to the absorber layer surface using spin coating (3000 rpm, 30 s). After pre-baking at 80℃ for 8 min, it is UV cured (365 nm, 300 mJ / cm²) to form a first sublayer with a thickness of 75 nm and a refractive index of 1.80. The second sublayer coating solution is then applied to the surface of the first sublayer using the same method to form a second sublayer with a thickness of 128 nm and a refractive index of 1.55. Finally, the third sublayer coating solution is applied to the surface of the second sublayer using the same method to form a third sublayer with a thickness of 102 nm and a refractive index of 1.28.

[0107] Experimental Example 2: The difference between this experimental example and Experiment 1 is that: The structure of the light absorber in Experiment Example 2 is as follows: Substrate → Absorbing layer (1.52) → First sublayer (1.62) → Second sublayer (1.91) → Third sublayer (1.72) → Fourth sublayer (1.55) → Outer layer (1.38) The preparation steps for Experiment Example 2 are as follows: Step 1: Same as in Experiment Example 1; Step 2: The difference from Experiment 1 is that the parameter combination obtained after screening based on process feasibility is as follows: the first sublayer has a target refractive index of 1.62 and a target thickness of 72 nm, the second sublayer has a target refractive index of 1.91 and a target thickness of 138 nm, the third sublayer has a target refractive index of 1.72 and a target thickness of 85 nm, the fourth sublayer has a target refractive index of 1.55 and a target thickness of 112 nm, and the outer layer has a target refractive index of 1.38 and a target thickness of 95 nm.

[0108] Step 3: Same as in Experiment Example 1, adjust the process parameters according to the target refractive index and target thickness.

[0109] Step 4: Same as in Experiment Example 1, adjust the process parameters according to the target refractive index and target thickness.

[0110] Step 5: Fabrication of the outer layer: A MgF2 thin film is deposited on the surface of the fourth sublayer using radio frequency magnetron sputtering with a base vacuum of 5 × 10⁻⁶. -4 Pa, Ar flow rate 30 sccm, working pressure 0.7 Pa, RF power 150 W, deposition rate 0.3 nm / s, film thickness monitored in real time by a quartz crystal microbalance, forming an outer layer with a thickness of 95 nm and a refractive index of 1.38.

[0111] Experimental Example 3: The difference between this experimental example and Experiment 1 is that: The structure of the light absorber in Experiment Example 3 is as follows: Substrate → Absorbing layer (1.52) → First sublayer (1.91) → Second sublayer (1.72) → Third sublayer (1.55) → Outer layer (1.38) The preparation steps for Experiment Example 3 are as follows: Step 1: Same as in Experiment Example 1; Step 2: The difference from Experiment 1 is that the parameter combination obtained after screening based on process feasibility is as follows: the first sublayer has a target refractive index of 1.91 and a target thickness of 125 nm, the second sublayer has a target refractive index of 1.72 and a target thickness of 92 nm, the third sublayer has a target refractive index of 1.55 and a target thickness of 108 nm, and the outer layer has a target refractive index of 1.38 and a target thickness of 95 nm.

[0112] Step 3: Same as in Experiment Example 1, adjust the process parameters according to the target refractive index and target thickness.

[0113] Step 4: Same as in Experiment Example 1, adjust the process parameters according to the target refractive index and target thickness.

[0114] Step 5: Fabrication of the outer layer: A MgF2 thin film is deposited on the surface of the fourth sublayer using radio frequency magnetron sputtering with a base vacuum of 5 × 10⁻⁶. -4 Pa, Ar flow rate 30 sccm, working pressure 0.7 Pa, RF power 150 W, deposition rate 0.3 nm / s, film thickness monitored in real time by a quartz crystal microbalance, forming an outer layer with a thickness of 95 nm and a refractive index of 1.38.

[0115] Experiment Example 4: The difference between this experimental example and Experiment 1 is that: The structure of the light absorber in Experiment Example 4 is as follows: Substrate → Absorbing layer (1.52) → First sublayer (1.62) → Second sublayer (1.91) → Outer layer (1.38) The preparation steps for Experiment Example 4 are as follows: Step 1: Same as in Experiment Example 1; Step 2: The difference from Experiment 1 is that the parameter combination obtained after screening based on process feasibility is: the target refractive index of the first sublayer is 1.62 and the target thickness is 76nm, and the target refractive index of the second sublayer is 1.91 and the target thickness is 134nm.

[0116] Step 3: Same as in Experiment Example 1, adjust the process parameters according to the target refractive index and target thickness.

[0117] Step 4: Same as in Experiment Example 1, adjust the process parameters according to the target refractive index and target thickness.

[0118] Step 5: Fabrication of the outer layer: A MgF2 thin film is deposited on the surface of the second sublayer using radio frequency magnetron sputtering, with a base vacuum of 5 × 10⁻⁶. -4 Pa, Ar flow rate 30 sccm, working pressure 0.7 Pa, RF power 150 W, deposition rate 0.3 nm / s, film thickness monitored in real time by a quartz crystal microbalance, forming an outer layer with a thickness of 95 nm and a refractive index of 1.38.

[0119] Comparative Example 1: The difference between this comparative example and Experimental Example 1 is that: The light absorber structure of Comparative Example 1 is as follows: Substrate → Absorbing layer (1.52) The preparation steps for Comparative Example 1 are as follows: Step 1: Same as in Experiment Example 1; Steps two, three, and four are not executed.

[0120] Comparative Example 2: The difference between this comparative example and Experimental Example 1 is that: The light absorber structure of Comparative Example 2 is as follows: Substrate → Absorber layer (1.52) → Single antireflective layer (1.72) → Outer layer (1.38) The preparation steps for Comparative Example 2 are as follows: Step 1: Same as in Experiment Example 1; Do not perform step two; Step 3: Same as in Experiment 1, based on the target refractive index of 1.72, weigh out the titanium dioxide dispersion (48wt% titanium dioxide) and mix it with the polymer matrix solution, add HDI curing agent, filter and degas to obtain a single antireflective coating solution.

[0121] Step 4: Coating and curing the single antireflective layer: Apply the antireflective coating liquid to the surface of the absorber layer by spin coating (3000 rpm, 30 s), pre-bake at 80℃ for 8 min, and then UV cure (365 nm, 300 mJ / cm²) to form a single antireflective layer with a thickness of 96 nm and a refractive index of 1.72.

[0122] Step 5: Fabrication of the outer layer: A MgF2 thin film is deposited on the surface of the single antireflection layer using radio frequency magnetron sputtering, with a base vacuum of 5×10⁻⁶. -4 Pa, Ar flow rate 30 sccm, working pressure 0.7 Pa, RF power 150 W, deposition rate 0.3 nm / s, film thickness monitored in real time by a quartz crystal microbalance, forming an outer layer with a thickness of 95 nm and a refractive index of 1.38.

[0123] Comparative Example 3: Commercial product Aeroglaze Z306.

[0124] Comparative Example 4: Commercial product: Acktar Spectral Black.

[0125] Comparative Example 5: Commercial product Vantablack S-VIS.

[0126] The reflectance spectrum in the 380nm-780nm band was measured using a UV-Vis-NIR spectrophotometer (equipped with an integrating sphere) under near-normal incidence conditions. The average reflectance and minimum reflectance were calculated. The coating adhesion grade was tested using the ISO 2409 cross-cut adhesion test. The test results are shown below: Table 1

[0127] Analysis of Table 1 shows that: The light absorber prepared in Example 2 exhibited the best optical performance: an average reflectance of 0.16% and a minimum reflectance of 0.04% at 578nm in the visible light band of 380nm-780nm; an average reflectance of 0.31% and a minimum reflectance of 0.09% at 605nm in Example 3; an average reflectance of 0.68% and a minimum reflectance of 0.23% at 642nm in Example 1; and an average reflectance of 0.43% and a minimum reflectance of 0.16% at 642nm in Example 4. All four samples achieved an adhesion rating of Grade 1 according to the ISO 2409 cross-cut adhesion test, indicating that the prepared light absorbers possess both near-zero reflectance optical properties and excellent mechanical stability. Comparing Experimental Example 1 with Comparative Example 1, it can be seen that Comparative Example 1 is a single-layer absorption layer structure without an antireflection layer, with an average reflectance of 4.27% and a minimum reflectance of 3.82% at 415 nm. The average reflectance of Comparative Example 1 is approximately 6 times that of Experimental Example 1, indicating that relying solely on the bulk absorption of the absorption layer cannot effectively suppress Fresnel reflection at the air-coating interface. The refractive index gradient structure of the antireflection layer plays a decisive role in reducing reflectance.

[0128] Comparing Experimental Example 1 and Comparative Example 2, it can be seen that Comparative Example 2, which uses a single-layer antireflection layer plus an outer layer structure, has an average reflectivity of 1.52% and a minimum reflectivity of 0.87% at 523 nm. The average reflectivity of Comparative Example 2 is approximately 2.2 times that of Experimental Example 1, indicating that the gradient antireflection layer composed of multiple sublayers achieves a better broadband antireflection effect than the single-layer antireflection layer under the same material system through the constructive / destructive interference effect between the sublayer interfaces.

[0129] Comparing Experiment 1 and Experiment 3, it can be seen that Experiment 3 adds an outer layer of MgF2 to the three-sublayer structure of Experiment 1. Its average reflectivity decreases from 0.68% to 0.31%, and its minimum reflectivity decreases from 0.23% to 0.09%. This indicates that the outer layer of MgF2 further improves the impedance matching between the outermost layer and the air, and effectively reduces residual reflection.

[0130] Comparing Experiment 1 and Experiment 4, it can be seen that Experiment 4 removed the third sublayer of Experiment 1 and added a MgF2 outer layer. Its average reflectivity decreased from 0.68% to 0.43%, and the minimum reflectivity decreased from 0.23% to 0.16%. This shows that the dry-prepared MgF2 outer layer has a better anti-reflection effect than the wet-prepared hollow silica anti-reflection sublayer.

[0131] Comparing Experiment 3 with Experiment 2, it can be seen that Experiment 2 added a fourth sublayer to the three-sublayer plus outer layer structure of Experiment 3. Its average reflectivity decreased from 0.31% to 0.16%, and its minimum reflectivity decreased from 0.09% to 0.04%. This shows that increasing the number of sublayers provides greater design freedom for global optimization of TMM, making the anti-reflection profile closer to the theoretical optimal solution, and further improving the broadband anti-reflection performance.

[0132] Comparing Experimental Example 3 with Comparative Example 3, it can be seen that the reflectivity of Example 3 is reduced by more than an order of magnitude compared to the traditional aviation black paint Aeroglaze Z306 (average reflectivity of about 4.8%).

[0133] Comparing Experiment 3 with Comparative Example 4, it can be seen that, compared with the Spectral Black inorganic vacuum coating from Israel's Acktar Company, the average reflectivity of Example 3 is reduced by about 3 times, and the minimum reflectivity is reduced by more than 5 times.

[0134] Comparing Experiment 3 with Comparative Example 5, it can be seen that the optical performance of Example 3 is on par with the Vantablack S-VIS carbon nanotube array ultra-black coating from Surrey NanoSystems in the UK. However, the ultra-low reflectivity of Comparative Example 5 depends on the high aspect ratio vertically arranged carbon nanotube array structure. This structure is prone to collapse and detachment under external impact, friction, or environmental corrosion, and its adhesion is far lower than that of commercial coatings. Furthermore, its preparation requires specialized chemical vapor deposition equipment, making it difficult to apply over large areas.

[0135] Regarding adhesion, Examples 1-3 and Comparative Examples 1-4 both achieved ISO 2409 Grade 1 (coating peeling area < 5%), while Comparative Example 5 only achieved Grade 5 (the worst grade), confirming the structural defect of its high aspect ratio carbon nanotube array being prone to collapse and peeling. This demonstrates that the present invention, by replacing the micro / nano array structure with a continuous dense film, achieves optical performance comparable to that of an ultra-black array coating while retaining the mechanical stability of a commercial-grade coating.

[0136] In summary, the test results of the above experimental examples and comparative examples demonstrate that the preparation method of the present invention, through the systematic synergy of a functionally separated absorption layer + antireflection layer, TMM and global optimization algorithm to determine the combination of refractive index and thickness parameters, and composite surface modification process of silane coupling agent and phosphate ester dispersant, enables the prepared light absorber to possess near-zero reflection optical performance with an average reflectance of 0.43% and a minimum reflectance of 0.16%@642nm, as well as mechanical stability of ISO 2409 Grade 1. This makes it suitable for applications such as photoelectric detection, imaging display, semiconductor devices, and precision optical systems.

[0137] The foregoing has provided a detailed description of a light absorber, its preparation method, and its applications as disclosed in the embodiments of the present invention. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention. Any modifications, equivalent substitutions, and improvements made within the principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A light absorber, characterized in that: It includes an absorption layer and an anti-reflection layer disposed on the surface of the absorption layer; The absorption layer is composed of a polymer matrix and nano-absorbing units; the refractive index of the absorption layer is 1.48-1.

55. The antireflective layer comprises multiple sublayers stacked sequentially; each sublayer is composed of a polymer matrix and oxide particles, and by designing different types and / or mass fractions of oxide particles, each sublayer has a different refractive index, and the refractive index of each sublayer varies in a gradient along the stacking direction; the refractive index of each sublayer is 1.20-1.

91.

2. The light absorber as described in claim 1, characterized in that: It also includes the outer layer; The outer layer is disposed on the side of the antireflection layer away from the absorption layer; the outer layer is a MgF2 thin film.

3. The light absorber as described in claim 1, characterized in that: It includes an absorption layer, a first sublayer, a second sublayer, and an outer layer stacked in sequence; The absorption layer is a composite film incorporating carbon black nanoparticles. The thickness of the absorption layer is 300nm-800nm. In the optical wavelength range of 380nm-780nm, the real part of the equivalent complex refractive index is 1.48-1.55 and the imaginary part is 0.002-0.

01. The first sublayer is a composite film incorporating titanium dioxide, wherein the average particle size of the titanium dioxide is 10nm-20nm and the mass fraction is 30wt%-40wt%; the thickness of the first sublayer is 70nm-80nm, and the refractive index is 1.60-1.64 in the optical wavelength range of 380nm-780nm; The second sublayer is a composite film incorporating titanium dioxide, wherein the average particle size of the titanium dioxide is 10nm-20nm and the mass fraction is 68wt%-78wt%; the thickness of the second sublayer is 125nm-145nm, and the refractive index is 1.89-1.91 in the optical wavelength range of 380nm-780nm; The outer layer is a MgF2 thin film with a thickness of 80nm-110nm and a refractive index of 1.38 in the optical wavelength range of 380nm-780nm.

4. A method for preparing a light absorber as described in claim 1, characterized in that: Includes the following steps: The absorber layer was prepared using a wet process. A nano-absorbing unit and a polymer matrix are used to prepare an absorption layer coating liquid; the absorption layer coating liquid is coated on the substrate surface and cured to form an absorption layer; Antireflection layer prepared by wet process: The target refractive index and target thickness of each sublayer in the antireflection layer are obtained by using TMM and global optimization algorithms; Based on the target refractive index, oxide particles are mixed with a polymer matrix, and a multilayer coating solution is obtained by adjusting the type and / or mass fraction of oxide particles. as well as Based on the target thickness, multiple sublayer coating liquids are coated and cured on the side of the absorption layer opposite to the substrate to construct multiple sublayers with different refractive indices, forming an antireflection layer composed of multiple sublayers.

5. The method for preparing the light absorber as described in claim 4, characterized in that: The absorber layer is prepared using a wet process, specifically including the following steps: The nano-absorbing units are mixed with the polymer matrix to obtain an absorption layer mixture; the nano-absorbing units account for 0.5 wt%-10 wt% of the total mass of the absorption layer mixture. Add a curing agent to the absorbent layer mixture and mix thoroughly to obtain an absorbent layer coating liquid with a dynamic viscosity of 50 mPa·s-500 mPa·s; and The absorbent coating liquid is applied to the surface of the substrate and then cured to form the absorbent layer.

6. The method for preparing the light absorber as described in claim 5, characterized in that: The nano-absorbing units are mixed with the polymer matrix to obtain the absorption layer mixture, which specifically includes the following steps: A polymer matrix solution was prepared by dissolving the polymer matrix in a mixed solvent, wherein the solid content of the polymer matrix was 15 wt%–30 wt%. The nano-light-absorbing unit is subjected to surface functionalization treatment to form an organic modification layer containing reactive functional groups on the surface of the nano-light-absorbing unit. The reactive functional groups are selected from at least one of carbon-carbon double bonds, carboxyl groups, hydroxyl groups, and silanol groups. The surface-functionalized nano-absorbing units were added to a mixed solvent and centrifuged to obtain a nano-absorbing unit premix. The premixed solution is placed in an ultrasonic cell disruptor, and the nano-absorbing unit aggregates are broken up by jet injection to achieve a primary particle dispersion, resulting in a nano-absorbing unit dispersion. The polydispersity index of this primary particle dispersion is no higher than 0.

15. The nano-absorbing unit dispersion was added to the polymer matrix solution, and the mixture was then used to obtain the absorption layer mixture.

7. The method for preparing the light absorber as described in claim 4, characterized in that: The target refractive index and target thickness of each sublayer in the antireflection layer are obtained through TMM and global optimization algorithms, specifically including the following steps: A candidate set is established based on the parameter combinations of refractive index and thickness that can be fabricated for each sublayer; Based on the MG model and the volume fraction of the nano-absorbing units in the absorption layer, the complex refractive index of the absorption layer is calculated, and the complex refractive index of the absorption layer is used as the terminal admittance. The refractive index and thickness of each sublayer are used as design variables to construct an objective function with the goal of achieving the minimum average reflectance of the wavelength band in which the light to be absorbed is located. The spectral reflectance of the parameter combinations in the candidate set is calculated using TMM, and the average reflectance is obtained by integration, which is used as the fitness in the global optimization algorithm. A global optimization algorithm is used to find the parameter combination that minimizes the reflection loss of the absorbed light; and Based on process feasibility, the target refractive index and target thickness of each sublayer were obtained after screening.

8. The method for preparing the light absorber as described in claim 4, characterized in that: Based on the target refractive index, oxide particles are mixed with a polymer matrix. By adjusting the type and / or mass fraction of the oxide particles, a multi-layer coating solution is obtained. The specific steps include: A polymer matrix solution is prepared by dissolving the polymer matrix in a mixed solvent; The oxide particles are then surface-modified. Surface-modified oxide particles are added to a mixed solvent and dispersed to obtain an oxide particle dispersion; and Based on the target refractive index, the oxide particle dispersion was weighed and mixed with the polymer matrix to prepare multiple sublayer coating liquids that can construct sublayers with different refractive indices.

9. The method for preparing the light absorber as described in claim 8, characterized in that: Surface modification of the oxide particles specifically includes: The oxide particles are surface-modified using a silane coupling agent and a phosphate dispersant; the silanol groups in the silane coupling agent undergo a condensation reaction with the hydroxyl groups on the surface of the oxide particles to form covalent bonds; and the phosphate groups in the phosphate dispersant form coordination bonds with the surface of the oxide particles.

10. The application of any of the light absorbers described in claims 1-3 in photoelectric detection, imaging display, semiconductor devices and precision optical systems.